Can integrated clinical simulation trainings improve person-centred maternity care? Results from a pilot project in Ghana - P Afulani, PhD; R Aborigo, PhD; S Cohen, DNP; C Moyer, PhD; D Walker, MD; J Williams, PhD (Elsevier, 2019)
Background: Person-centred maternity care (PCMC) is maternity care that is responsive to and respectful of women's needs and values. It is a key dimension of quality, capturing the experience of interpersonal dimensions of care. Poor PCMC contributes to high maternal mortality not only directly but also indirectly through decreased demand for services. Although there is growing recognition of the importance of PCMC to maternal and child health outcomes, there is a paucity of data on interventions that aim to integrate a person-centred approach to maternity care. In this study, we aimed to evaluate the effect of an integrated simulation training on provision of PCMC. Methods: The pilot PCMC training project was launched in a rural district in Northern Ghana in April, 2017. To improve quality of care, including PCMC, we integrated specific components of such care, emphasising dignity and respect, communication and autonomy, and supportive care, into a simulation training to improve identification and management of obstetric and neonatal emergencies. 43 providers in the district participated in two 2-day trainings led by PRONTO international trainers. Six providers were then trained as simulation facilitators, and they led refresher sessions every month for 4 months at the five highest-volume delivery facilities in the district. We conducted surveys at baseline and endline with women who had recently given birth to assess their experiences of care using a 24-item version of the 30-item PCMC scale. Findings: We included data from 215 baseline surveys, conducted in March and April, 2017, and 318 surveys at endline in November, 2017. Women at endline reported higher PCMC scores than did women at baseline. The average PCMC score increased from 35·9 (SD 6·3) at baseline to 51·5 (12·9) at endline, a change of 43% (p<0·001). Scores on the subscales also increased between baseline and endline: from 13·6 (2·4) to 15·7 (3·3) for dignity and respect (p<0·001), 8·3 (3·2) to 15·6 (6·5) for communication and autonomy (p<0·001), and 14·0 (3·5) to 20·3 (5·1) for supportive care (p<0·001). The greatest increase was in communication and autonomy which increased by 87%. These differences remain significant (p<0·001) in multilevel multivariate analysis controlling for several potential confounders and accounting for clustering at the facility level. Interpretation: Our findings suggest that integrated training that gives health-care providers the opportunity to learn, practise, and reflect on their provision of PCMC has the potential to improve care in low-resource settings. Incorporating such trainings into pre-service and in-service training of providers will help advance global efforts to promote PCMC. Funding: USAID Systems for Health.